(untitled) (Comprehensive Journal of Science, 2026)
The term "renewal" is an archaic term in Islamic texts and Islamic heritage, and its meaning is limited in some writings to specific issues of Sharia rulings, especially when renewal is related to the tool of thought directly connected to it, which is the mind. Its original meaning and contemporary uses extend to all aspects of life, when it is necessary to start from an Islamic religious reference in understanding these matters, in the political, economic, social, educational and other fields, or to develop an Islamic methodology in dealing with these matters. In this context, we find other terms and expressions besides the term “renewal” that have been used with meanings that do not stray far from the meaning of renewal, especially in the field of application and practical practice. These include the terms “reform,” “change,” “revival,” “rebirth,” and “reconstruction.” Thus, the call for renewal has become the goal of everyone who seeks to innovate in religion and seeks to triumph over a thought or opinion.